Language change : progress or decay ? - Aitchison, Jean. (London : Fontana press., 1981)
This lucid and up-to-date overview of language change. It discusses where our evidence about language change comes from, how and why changes happen, and how languages begin and end. It considers both changes which occurred long ago, and those currently in progress. It does this within the framework of one central question - is language change a symptom of progress or decay? It concludes that language is neither progressing nor decaying, but that an understanding of the factors surrounding change is essential for anyone concerned about language alteration. For this substantially revised third edition, Jean Aitchison has included two new chapters on change of meaning and grammaticalization. -- Publisher description.
Includes bibliography and index.
Keywords: Language